The efficiency of vehicle monitoring locations for a voluntary travel demand management program - Ko, Joonho; Kim, Daejin; Sin, Heung G.; Lee, Seungjae (Transport, 2014)
As many people are concerned about sustainable urban transportation systems, Travel Demand Management (TDM) is getting more attention as a viable option to reduce automobile dependency on an efficient way. Especially, voluntary participation-based TDM by offering incentives has been applied in many cities in recent years. The city of Seoul with 10 million population is offering incentives including an annual vehicle tax discount to increase the participation of Weekly No-driving Day (WND) program, a voluntary TDM program encouraging drivers to leave their cars home at least one weekday a week. The compliance of the program rule is monitored by Radio-Frequency IDentification (RFID) systems. In this study, to check the efficiency of the RFID monitoring system, the flow capturing location model is utilized to evaluate the adequateness of the RFID reader locations. Also, this paper proposes an optimal detection rate for the WND program based on economic evaluation results in consideration of costs and benefits of the program.First Published Online: 22 Sep 2014